Josephson and spontaneous currents at the interface between two d-wave superconductors with transport current in the banks - Kolesnichenko, Yu.A.; Omelyanchouk, A.N.; Shevchenko, S.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
A stationary Josephson effect in the ballistic contact of two d-wave superconductors with different orientation of the axes and with transport current in the banks is considered theoretically. We study the influence of the transport current on the current–phase relation of the Josephson and tangential currents at the interface. It is demonstrated that the spontaneous surface current at the interface depends on the transport current in the banks due to the interference of the angle-dependent condensate wave functions of the two superconductors.